The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1415-47572011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Towards an optimal sampling strategy for assessing genetic variation within and among white clover (Trifolium repens L.) cultivars using AFLP

Abstract: Cost reduction in plant breeding and conservation programs depends largely on correctly defining the minimal sample size required for the trustworthy assessment of intra- and inter-cultivar genetic variation. White clover, an important pasture legume, was chosen for studying this aspect. In clonal plants, such as the aforementioned, an appropriate sampling scheme eliminates the redundant analysis of identical genotypes. The aim was to define an optimal sampling strategy, i.e., the minimum sample size and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
3
9
0
1
Order By: Relevance
“…Although resampling suggested that uneven sampling sizes did not bias our genetic estimates, we would expect if bias was present, sampling too few plants would have underestimated diversity. Although we sampled fewer plants in 1995, compared to 2004 and 2009, 20 individuals were determined to be adequate to assess genetic variation in T. repens , also an insect-pollinated outcrossing perennial species [69]. Our results were also consistent with field observations.…”
Section: Discussionsupporting
confidence: 75%
“…Although resampling suggested that uneven sampling sizes did not bias our genetic estimates, we would expect if bias was present, sampling too few plants would have underestimated diversity. Although we sampled fewer plants in 1995, compared to 2004 and 2009, 20 individuals were determined to be adequate to assess genetic variation in T. repens , also an insect-pollinated outcrossing perennial species [69]. Our results were also consistent with field observations.…”
Section: Discussionsupporting
confidence: 75%
“…The differences of average gene diversity between central and peripheral populations were not significant for any of the drought-induced genes used as probes. Khanlou et al (2011) using AFLP markers in three cultivars of T. repens measured genetic diversity values of 0.319, 0.289 and 0.272 for different cultivars, which are similar to the ones found in this study.…”
Section: Resultssupporting
confidence: 87%
“…Nei's diversity index is often used in population genetic studies, though it is based exclusively on allele frequency and relies on Hardy-Weinberg Equilibrium (HWE). On the other hand, Shannon index is calculated based on allele richness considering both the number and frequency of the alleles, consequently not assuming HWE [17]. Both indexes were calculated for comparison with other studies.…”
Section: Methodsmentioning
confidence: 99%